Student Response of The Integrated Biology E-Modul Imtaq Values on Vertebrate Material - Widianti, Sara; Robiah, Siti (Universitas Lampung, 2023)
This study aims to determine the student's response to the electronic module product of integrated vertebrate material imtaq values that have been developed. This research was a research and development (R&D) using a modified Analysis, Design, Development, Implementation and evaluation (ADDIE) model, but this research only reached the Development stage. Determination of student samples by purposive sampling with a sample of 60 students from 3 schools. Student responses were obtained through limited trials at SMA Negeri 1 Tapung Hilir, MA Roudhotul Hidayah, and MA Al-Falah. Data was collected through observation, documentation, interviews, and student response questionnaires. The data is analyzed descriptively. The results showed that the developed e-module received a very good response from students with an average of 95.67%. Thus, the developed E-module can proceed to the stage of wide-scale trials. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28431